The yeast mitochondrial F1F0-ATP synthase is a multisubunit complex that contains at least 17 different subunits. Subunit 8 of yeast mitochondrial ATP synthase is a hydrophobic protein of 48 amino acids encoded by the mitochondrial ATP8 gene. A dual control allotopic expression system for subunit 8 has been developed. The strategy involves maintenance of two different compatible yeast expression vectors each utilizing a different inducible promoter in the same host cells. The system thus enables - I MADE ARTIKA (HAYATI Journal of Biosciences, 2011)
The yeast mitochondrial F1F0-ATP synthase is a multisubunit complex that contains at least 17 different subunits. Subunit 8 of yeast mitochondrial ATP synthase is a hydrophobic protein of 48 amino acids encoded by the mitochondrial ATP8 gene. A dual control allotopic expression system for subunit 8 has been developed. The strategy involves maintenance of two different compatible yeast expression vectors each utilizing a different inducible promoter in the same host cells. The system thus enables cloning and allotopic expression of two different forms of subunit 8 gene. The goal of the developed strategy is to permit allotopic expression of functional wildtype subunit 8 gene under a conditional promoter system and subunit 8 variant gene under the control of a different promoter system. The system is potentially useful for accurate assessment of assembly behavior of functionally defective subunit 8 variants in vivo. The strategy relies on the ability to conditionally regulate the expression of the two genes. A set of functionally defective subunit 8 variants has been cloned under an inducible yeast promoter system and dual plasmid harboring strains for dual control allotopic expression of each variant have been constructed.